"Post‐Truth, " "Alternative Facts" and "Fakenomics". (12th January 2018) - Keeton, Gavin
Abstract: South African companies are accused of hoarding profits to accumulate large amounts of "idle" cash, as well as of being the perpetrators of massive illegal capital flight. This paper argues that much of the claimed corporate cash is either offshore or belongs to banks. It reminds that bank deposits increase when companies borrow, not when they retain profits. It shows, too, that measures of massive capital flight actually reflect data errors. Exaggerating, through faulty methodology the extent to which companies have cash or may be involved in illegal capital flight is unhelpful. It exacerbates already‐fraught government‐business relations, and complicates the search for solutions to South Africa's economic problems.